#### Answer

n = -4

#### Work Step by Step

3n - 5 = 7n + 11
First, you need to get the variable (n) on one side of the equation, so subtract 3n from both sides of the equation. This will remove the n from the left side of the equation.
3n - 5 - 3n = 7n + 11 - 3n
Simplify to get this:
-5 = 4n + 11
Subtract 11 from each side.
-5 - 11 = 4n + 11 - 11
Simplify to get:
-16 = 4n
Divide each side by 4.
$\frac{-16}{4}$ = $\frac{4n}{4}$
Simplify to n = -4
We check our answer to find that our answer is, indeed, correct.